Broccoli sprouts in analgesia – preclinical in vivo studies. Issue 1 (14th December 2016) - Baenas, Nieves; González-Trujano, María Eva; Guadarrama-Enríquez, Omar; Pellicer, Francisco; García-Viguera, Cristina; Moreno, Diego A.
Abstract : Broccoli sprouts produce significant and dose-dependent antinociceptive activity involving an opioid mechanism without sedative or gastric damage. Abstract : Background : Broccoli is a rich source of health-promoting glucosinolates, phenolic compounds, minerals and vitamins, which might have potential to alleviate pain. Aim : To explore the antinociceptive effects of a broccoli sprout aqueous extract (BSE) in experimental models of pain and an opioid mechanism . Materials and methods : the BSE was administered to mice and rats that were subjected to the writhing and formalin tests, respectively. Gastric damage or sedative-like response, as adverse effects observed in anti-inflammatory non-steroidal and opioid analgesic drugs, respectively, were also explored. Results : Antinociception, but not sedative or gastric injury response, was observed in a significant and dose-dependent manner with the BSE (50–500 mg kg −1, i.p. and 500–2000 mg kg −1, p.o.) in comparison to the control group; these effects resembled those observed with the analgesic tramadol (30 mg kg −1, i.p.) in writhing and formalin assessments. Blockage of opioid receptors by naloxone (1 mg kg −1, i.p.) produced partial inhibition of the antinociceptive effect of the BSE in both assays. Conclusion : This study gives evidence of the potential activity of broccoli sprouts in pain therapy.